Insect Media : An Archaeology of Animals and Technology - Parikka, Jussi, 1976- (Book collections on Project MUSE., 2010)
Since the early nineteenth century, when entomologists first popularized the unique biological and behavioral characteristics of insects, technological innovators and theorists have proposed insects as templates for a wide range of technologies. In Insect Media, Jussi Parikka analyzes how insect forms of social organization-swarms, hives, webs, and distributed intelligence-have been used to structure modern media technologies and the network society, providing a radical new perspective on the interconnection of biology and technology. Through close engagement with the pioneering work of insect ethologists, including Jakob von Uexkull and Karl von Frisch, posthumanist philosophers, media theorists, and contemporary filmmakers and artists, Parikka develops and insect theory of media, one taht conceptualizes modern media as more than the products of individual human actors, social interests, or technological determinants. They are, rather, profoundly nonhuman phenomena that both draw on and mimic the alien lifeworlds of insects.